Stratigraphic Characteristics and Sediment-Filling Process of the Early Permian Fengcheng Formation in the Northwestern Margin of the Junggar Basin, Northwest China - Zhi, Dongming; Liu, Mingxin; Chen, Xinwei; Said, Nuru; Tang, Wenbin; Hu, Chenhui; Qin, Zhijun; Zou, Hao; Gong, Deyu (Frontiers in Earth Science, 2022)
The Permian Fengcheng Formation in the Mahu sag of the Junggar Basin is a crude oil reservoir and source rock. However, its stratigraphic characteristics, the boundary marks of the three members (lower, middle, and upper), and the sediment-filling processes are unclear. This study presents the sedimentary systems and sediment-filling processes in an intracontinental rift basin of this area using sedimentary-faces analysis, sequence stratigraphy, well logs, and two-dimensional seismic interpretations. The results show that the Fengcheng Formation consists of three third-order sequence stratigraphy (SQf1, SQf2, and SQf3). The lowest member of the Fengcheng Formation is composed of gray to dark gray thin middle layers of tuff, lacustrine dolomitic mudstone, and argillaceous dolomite near the depocenter. Tuff, siltstone, a small amount of fan–delta glutenite, volcanic breccia, and basalt are present near the fault zone. The logging curve is characterized by a high gamma-ray (GR) value, high amplitude, wavelength growth, and medium frequency. Near the depocenter, the middle member of the Fengcheng Formation comprises gray and gray–black thin layers of lacustrine muddy dolomite and dolomitic mudstone and thin sandstone and mudstone interbedded between tuff and gravel near the orogenic belt. The logging curve displays high-to-low GR values, high amplitude, short wavelength, and high frequency. The upper member of the Fengcheng Formation is not characterized by lesser tuffaceous and dolomitic components but by an increased fan–delta sandy content. Next, the bottom of the upper member is composed of lacustrine mudstone and siltstone interbedded between dolomitic mudstones; whereas, the top of the upper member is dominated by fan–delta coarse sandstone and sandy conglomerate. The logging curve shows low GR values, small amplitude, and continuous stability. The sediment-filling process of the Fengcheng Formation is controlled by fault activity. Overall, the lower and middle members of the Fengcheng Formation expand during the sediment-filling process of the lake basin of the Mahu sag; whereas, the upper member contracts. The strong uplift of the Horst near the Baiquan and Mahu orogenic belts led to an increase in provenance supply, resulting in a contraction of the southwestern margin of the lake basin during the sedimentation period from lower member to upper member of Fengcheng Formation.